Arginine-vasotocin expression and participation in reproduction and social behavior in males of the cichlid fish Cichlasoma dimerus - Ramallo, Martín Roberto (2012)
In non-mammalian vertebrates, the nonapeptide arginine-vasotocin (AVT) is involved in the regulation of social behavior related to reproduction and aggression. The cichlid fish Cichlasoma dimerus is a monogamous species with complex social hierarchies. Males are found in one of two basic alternative phenotypes: Non-territorial and territorial males. In this work we characterize the vasotocinergic system in males of C. dimerus in relation to social status with particular emphasis on the various putative sites of action of AVT across the hypothalamic–pituitary–gonad (HPG) axis, and its effects on reproductive and social behavior. The location and distribution of vasotocinergic neurons in the brain was studied, highlighting a morphometric analysis of AVT producing neurons in males of different social status. The effect of AVT on pituitary gonadotropin secretion was analyzed by single pituitary culture while expression of AVT in peripheral organs was studied by RT-PCR using specific primers. Finally, the role of AVT on testicular androgen release was assessed by in vitro incubation of testis. Results showed a positive effect of AVT on gonadotropin secretion, where β-LH showcased a triphasic response under increasing AVT concentration, while β-FSH’s response was dose-dependent and directly proportional. AVT showed a positive and concentration-dependent effect over testicular androgens synthesis and secretion in vitro. Vasotocin expression was observed in testicular somatic tissue located in the interstitial compartment. Thus, the AVT system in C. dimerus appears to be of high complexity, with multiple sites of action in the hypothalamus–pituitary–gonadal axis.